Cell Surface Binding and Lipid Interactions behind Chemotherapy-Drug-Induced Ion Pore Formation in Membranes - Ashrafuzzaman, Md. (Membranes (Basel), 2021)
Chemotherapy drugs (CDs) disrupt the lipid membrane’s insulation properties by inducing stable ion pores across bilayer membranes. The underlying molecular mechanisms behind pore formation have been revealed in this study using several methods that confirm molecular interactions and detect associated energetics of drugs on the cell surface in general and in lipid bilayers in particular. Liposome adsorption and cell surface binding of CD colchicine has been demonstrated experimentally. Buffer dissolved CDs were considerably adsorbed in the incubated phospholipid liposomes, measured using the patented ‘direct detection method’. The drug adsorption process is regulated by the membrane environment, demonstrated in cholesterol-containing liposomes. We then detailed the phenomenology and energetics of the low nanoscale dimension cell surface (membrane) drug distribution, using atomic force microscopy (AFM) imaging what addresses the surface morphology and measures adhesion force (reducible to adhesive energy). Liposome adsorption and cell surface binding data helped model the cell surface drug distribution. The underlying molecular interactions behind surface binding energetics of drugs have been addressed in silico numerical computations (NCs) utilizing the screened Coulomb interactions among charges in a drug–drug/lipid cluster. Molecular dynamics (MD) simulations of the CD-lipid complexes detected primarily important CD-lipid electrostatic and van der Waals (vdW) interaction energies. From the energetics point of view, both liposome and cell surface membrane adsorption of drugs are therefore obvious findings. Colchicine treated cell surface AFM images provide a few important phenomenological conclusions, such as drugs bind generally with the cell surface, bind independently as well as in clusters of various sizes in random cell surface locations. The related adhesion energy decreases with increasing drug cluster size before saturating for larger clusters. MD simulation detected electrostatic and vdW and NC-derived charge-based interactions explain molecularly of the cause of cell surface binding of drugs. The membrane binding/association of drugs may help create drug–lipid complexes with specific energetics and statistically lead to the creation of ion channels. We reveal here crucial molecular understanding and features of the pore formation inside lipid membranes that may be applied universally for most of the pore-forming existing agents and novel candidate drugs.